Vertical and Oblique Ionosphere Sounding During the 21 August 2017 Solar Eclipse - Terence Bullett; Justin Mabie (Geophysical Research Letters)
Abstract On 21 August 2017, a total solar eclipse crossed North America. Two Vertical Incident Pulsed Ionospheric Radar ionosondes were operated, one deployed under totality at Lusk, Wyoming, and another south of totality, 313 km away from the geomagnetic meridian in Boulder, Colorado. The two Vertical Incident Pulsed Ionospheric Radar systems were synchronized for precise observation of both vertical and oblique group and phase paths. Hand‐scaled values of virtual heights and critical frequencies are presented. Arrival angles were computed using phase interferometry and used to compute equivalent vertical critical frequencies at the oblique midpoint. Oblique propagation geometry and horizontal gradients allowed measurement of F2 layer during ionosphere G condition where foF1 exceed foF2 after totality.